Small stories and extended narratives on Twitter. (December 2015) - Dayter, Daria
Abstract: This article investigates narrative practices on Twitter. The qualitative analysis is based on the corpus of 1000 tweets sampled from the timelines of 11 Anglophone users. The users form a diffuse community united by an interest in ballet as a physical activity and an art. Storytelling emerged as one of important tools for identity construction, although Twitter stories differ from a prototypical narrative on several levels. These differences are examined from three theoretical angles: the structural approach (Labov and Waletzky, 1967. Narrative analysis: oral versions of personal experience. In: Helm, J. (Ed.), Essays on the Verbal and Visual Arts. Proceedings of the 1966 Annual Spring Meeting. Distributed by the University of Washington Press, Seattle, pp. 12–44), the dimensional approach (Ochs and Capps, 2001. Living Narrative: Creating Lives in Everyday Storytelling. Cambridge, MA, Harvard UP), and the small stories framework (Georgakopoulou, 2007a. Small Stories, Interaction and Identities. Benjamins, Amsterdam). Along with multi-tweet stories that can be analysed into orientation, complication, evaluation and resolution, two kinds of stories typical for the eyewitness microgenre were present. The first of these is a delayed resolution narrative, i.e. live commentary that obtains the integrity of a single narrative only post-factum. The second type is a tiny story, i.e. a fragmentary, minimally newsworthy report on everyday activities with unclear narrative stance. Highlights: Investigation of a discourse community of ballet enthusiasts on Twitter. Stories are told in single tweets and across multiple tweets. Some Twitter narratives contain traditional elements of a narrative. Breaking news is the most common category. Delayed resolution narrative and tiny story as subtypes of breaking news.